New species of the family Julidae Leach 1814 from Altai, Russia (Diplopoda, Julida) - Mikhaljova, Elena V. (Zootaxa, 2009)
Three new species of the millipede family Julidae Leach 1814 are described from the Republic of Altai, Siberia, Russia: Julus azarovae sp. n., Julus insolitus sp.n. and Sibiriulus rectangulus sp.n.